Combination therapy with chitosan/siRNA nanoplexes targeting PDGF-D and PDGFR-beta reveals anticancer effect in breast cancer - Şalva, Emine; Özbaş, Suna; Alan, Saadet; Özkan, Naziye; Ekentok Atıcı, Ceyda; Kabasakal, Levent; Akbuğa, Jülide (Wiley, 2023)
Background: Platelet derived growth factors (PDGF)-D and the expression of its receptor increase in neoplastic progression of cancer. Co-silencing of growth factor and receptor can be suggested as an important strategy for effective cancer therapy. In the present study, we hypothesized that suppression of PDGF-D signaling pathway with small interfering RNAs (siRNAs) targeting both PDGF-D and PDGF receptor (PDGFR)-beta is a promising strategy for anticancer therapy. Methods: Chitosan nanoplexes containing dual and single siRNA were prepared at different weight ratios and controlled by gel retardation assay. Characterization, cellular uptake, gene silencing and invasion studies were performed. The effect of nanoplexes on breast tumor growth, PDGF expression and apoptosis was investigated. Results: We have shown that downregulation of PDGF-D and PDGFR-beta with chitosan/siRNA nanoplex formulations reduced proliferation and invasion in breast cancer cells. In the in vivo breast tumor model, it was determined that the intratumoral administration of chitosan/siPDGF-D/siPDGFR-beta nanoplexes markedly decreased the tumor volume and PDGF-D and PDGFR-beta mRNA and protein expression levels and increased apoptosis. Conclusions: According to the results obtained, we evaluated the effect of PDGF-D and PDGFR-beta on breast tumor development and showed that RNAi-mediated inhibition of this pathway formulated with chitosan nanoplexes can be considered as a new breast cancer therapy strategy.
Combination therapy with chitosan/siRNA nanoplexes targeting PDGF-D and PDGFR-? reveals anticancer effect in breast cancer
Keywords: Breast Cancer; Chitosan; PDGF-D; PDGFR-?; RNAi